EXPERIENCE AND TRAINING RELATE TO PERFORMANCE CLEAN AND HEALTHY LIVING BEHAVIOR IN CADRE IN THE WORKING AREA OF POASIA PRIMARY HEALTH CARE, KENDARI CITY: Clean and Healthy Living Behavior - Hasmariana; La Ode Saafi; Tasnim, Tasnim; Depu, Anry Hariadhin (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background:Southeast Sulawesi Provincial data shows that Community life behavior is measured by the number of households with a clean and healthy lifestyle which is based on predetermined indicators. In 2015, the percentage of Clean and Healthy Living Behaviors was 45%, in 2016 there was an increase of 52% and decreased in 2017 by 49% and in 2018 by 46%, while in 2019 there was an increase in the percentage of 53% again. Based on these data, the coverage was  still low because the target was set according to the minimum service standard was  80%. The orientation of community empowerment for health cadres is still insufficient, it is noted that only 36 people have received community empowerment training. The insufficient number of cadres can also make a negative contribution, resulting in the lack of achievement of the primary health care s program Methods:This type of research is a quantitative study, with a cross sectional study approach. The population of this study were  100 people and the  samples of this study were 80  cadres in 20 comprehensive health Post  in the working area of  Poasia primary health care centre in Kendari City. The sampling technique which was used in this study was a simple random sampling. Result: Based on the results of statistical tests show that the value (X2test) = 0.286 <X2table =3,841), meaning that there is no relationship between experience and performance of clean and healthy living behavior cadres. The household structures with Chi-square values ??(X2test) = 15,556> X2table =3,841, meaning that there is a relationship between training and the performance of clean and healthy living behavior cadres in household arrangements in the working area of ?? Poasia Primary health care centre in Kendari City. Conclusion:Cadres are expected to play an active role in increasing their knowledge and experience through training activities on cadre performance held by Puskesmas Poasia.